Medial opening-wedge high tibial osteotomy with microfracture in treatment of varus medial compartmental knee osteoarthritis: clinical outcomes and second-look arthroscopic results - Bai, Yunpeng; Lin, Binhui; Wang, Miao; Ding, Haoliang; Sun, Weibing; Sun, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: This study aimed to investigate the clinical outcomes of medial opening high tibial osteotomy (MOWHTO) combined with arthroscopic microfracture in the treatment of varus medial compartmental knee osteoarthritis and to assess cartilage regeneration using second-look arthroscopy.Methods: This study involved 86 patients (86 knees) who underwent MOWHTO and microfracture from August 2016 to August 2020, including 15 men and 71 women with an average age of 55.3±7.6 years (range, 42-71 years). The patients underwent a second-look arthroscopy to evaluate the status of cartilage regeneration at the time of plate removal, an average of 2 years after the initial osteotomy. Clinical and radiological examinations were performed preoperatively and at the final follow-up visit. The radiologic evaluation included the weight-bearing line ratio (WBL ratio), mechanical femorotibial angle (FTA), medial proximal tibial angle (MPTA), posterior tibial slope angle (PTS) and Kellgren-Lawrence (KL) grade. Clinical outcomes were assessed using the Knee Society score (KSS) and International Knee Documentation Committee (IKDC) scores. Arthroscopic findings were assessed by macroscopic evaluation of cartilage repair according to the International Cartilage Repair Society (ICRS) grading system.Results: The mean KSS and IKDC scores significantly improved at the final follow-up compared to the scores obtained preoperatively (P<0.05). At the time of plate removal, a second-look arthroscopic examination showed that the ICRS grade of the medial femoral condyle was as follows: grade I -11 cases, grade II -56, grade III-12, and grade IV-7, and cartilage regeneration was seen in 85% of knees (73/86). The ICRS grade of medial tibial plateau was grade I-12 cases, grade II-44, grade III-22, and grade IV-8, and cartilage regeneration was seen in 63% of knees (54/86). Significant differences were observed between cartilage regeneration and clinical outcomes (P<0.05). Clinical results were better in the good cartilage regeneration group (grades I and II) than were in the poor cartilage regeneration group (grades III and IV).Conclusion: MOWHTO combined with arthroscopic microfracture can effectively improve clinical outcomes in the treatment of varus medial compartmental knee osteoarthritis. Cartilage regeneration can be promoted by correcting varus deformities, which affect clinical outcomes.